(untitled) (Marketing Journal, 2025)
This scientific article analyzes the effective ness of personnel selection and evaluation mechanisms in higher education institutions, as well as their legal 52 foundations and impact on the quality of education. In higher education, the preparation of highly qualified specialists plays a crucial role. Therefore, it is essential to examine how the legal foundations of the personnel selection process, control mecha nisms, and their regulatory framework influence the effectiveness of this process. The article presents the results of research on the legal norms governing the recruitment process in higher education institutions, analyzes relevant regulatory documents, i nternal regulations of universities, and international experience. It discusses how the effective operation of the selection system, transparency, fair criteria, and the introduction of electronic technologies impact the quality of education. The article c oncludes with practical recommendations for improving personnel selection and evaluation mechanisms in the higher education system.